A promising set of candidate biomarkers of radioresistant prostate cancer - Mc Dermott, Niamh (Trinity College Dublin.School of Medicine.RADIATION THERAPY, 2016)
Radiotherapy (RT) has a prominent role when used as a single modality or in combination with androgen deprivation therapy in the management of prostate cancer (CaP) patients. However, even with currently available high-dose RT protocols, many patients develop recurrence or "biochemical failure" associated with a rise in prostate specific antigen (PSA), and ultimately reduced overall survival. As key regulators of cancer cell behavior, dysregulation of miRNAs expression is associated with both prostate cancer pathogenesis and treatment resistance. The identification of miRNA biomarkers have shown great promise in a number of cancers and in CaP show potential as both novel markers of radiation therapy failure and as targets for the re-sensitisation of radioresistant tumours. The overall aim of this thesis was the identification of novel biomarkers which may distinguish between a radio sensitive and resistant phenotype as a prerequisite for the future development of a novel pretreatment assay for the identification of radiotherapy prostate cancer patients at risk of biochemical failure. This was achieved through the generation of an isogenic model of resistance and subsequent miRNA microarray profiling of a panel of cell line models of radiation resistance. The development of in vitro isogenic models of radioresistance through exposure to fractionated radiation is an increasingly used approach to investigate the mechanisms of radioresistance in cancer cells and a valuable tool for biomarker discovery programs. An isogenic model of radioresistance of the 22Rv1 non-metastatic CaP cell line was generated using 2Gy fractionated ionising radiation to a cumulative dose of 60Gy. This process selected for 22Rv1 cells with increased proliferative potential following radiation exposure (1.3 fold increase in clonogenic survival after 2Gy and 2.2 fold increase after 10Gy) when compared to wild type and aged matched control 22Rv1 cells. This radiation resistant 22Rv1 model was enriched in S-phase cells, less susceptible to radiation-induced apoptosis and DNA damage coupled with increased repair capacity. Exposure to fractionated radiation progressively selected for 22Rv1 cells with enhanced oncogenic properties protective against radiation injury and supportive of tumour invasion. While this data must be considered within the context of one cell line, the phenotypic modifications observed support the clinical relevance of this model to enable further study of the mechanisms of radioresistance in prostate cancer cells. Microarray analysis of this model combined with hypoxic and cancer stem like cell models resulted in the selection and validation of a panel of miRNAs and the selection of hsa-miR-4284 as a potential novel marker of radioresistance in CaP. While re-expression of miR-4284 did not result in the re-sensitisation of radiation resistant cells to treatment, investigation of predicted downstream targets resulted in the identification of two targets: RLIM and RASGEFA1 as well as a potential key regulatory protein (YB-1). This work identifies a set of candidate biomarkers of radioresistant CaP with potential for the development of companion prognostic assays for radiotherapy CaP patients.
APPROVED
Keywords: Radiation Resistance; Prostate Cancer; Isogenic Cell Line